Analysis of the influence of changes in non-taxable income on the realization of tax revenues at the Raba Bima Pratama Tax Office - Yuliana, Astri; Munandar, Aris; Darmawan, Imam (Indonesia Auditing Research Journal, 2024)
This research uses quantitative analysis to measure the effect of changes in PTKP on the realization of tax revenues. The data used is secondary data obtained from the Raba Bima Pratama Tax Office, covering the 2019-2023 period. Data on Non-Taxable Income (PTKP) and realized tax revenues were transformed into natural logarithm (LN) form for statistical analysis. Regression analysis is used to measure the effect of changes in PTKP on the realization of tax revenues. From the regression analysis, the β coefficient value was obtained which shows the significance of the influence of PTKP on the realization of tax revenues. Data analysis for 2021 shows a decrease in PTKP which has an impact on increasing the realization of tax revenues. Based on the results of the analysis, future PTKP policy changes need to be considered carefully to ensure a balance between tax relief for taxpayers and stability of tax revenues. This research found that changes in PTKP had a significant influence on the realization of tax revenues at the Raba Bima Pratama Tax Office. The reduction in PTKP in 2021 will have an impact on increasing the realization of tax revenues, indicating that responsive and effective tax policies are very important to support the stability of tax revenues and sustainable economic development. Further research is needed to explore the influence of other factors such as inflation rates and economic growth on the realization of tax revenues.